MONITORING SYSTEM DESIGN SYSTEM AS MEASURING TEMPERATURE MEASURES - Prima Prayuda; Aries Boedi Setiawan; Nova Suryangga (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Monitoring system tool as a temperature gauge in the field is a tool that serves as a temperature gauge this happens there are several factors that first the temperature, humidity, and light intensity in the ranks of the Army is still using the manual way. In this tool uses 3 sensors that have 4 parameters of interconnected results to generate index data. The usefulness of each sensor is SHT11 as a temperature and humidity gauge, TSL2591 as a light meter, and anemometer as a wind speed gauge. This tool can serve as a wind speed gauge on a jumping workout.